Empowerment of patients and communication with health care professionals through an electronic health record - Ückert, Frank (International journal of medical informatics, 2003)
Objective: The aim of this project was to design and develop a personal electronic health record (EHR) in order to support patient empowerment and additionally to enhance their communication and information exchange with health professionals through this EHR. Method: The functionality of a personal Electronic Healthcare Record (EHR) may vary from a simple web-based interface for interactive data entry and data review up to a much more powerful system additionally supporting electronic data/document communication between clinical information systems of primary care practitioners or hospitals and even reminder based support for the empowered citizen, to actively take care of his health, based on relevant disease management programs. It is one means to support patient empowerment, additionally supported by tools for building a patient community. Since storage and communication of data in an EHR comprises sensible personal health data, each of those functions needs specific security and access management requirements to be considered and implemented. Result: Clinical pilot projects are already done or under development.
Available online 5 June 2003
Gesehen am 20.06.2018